Evaluating Sustainable Food System Innovations: A Global Toolkit for Cities - Élodie Valette; Alison Blay-Palmer; Beatrice Intoppa; Amanda Di Battista; Ophélie Roudelle; Géraldine Chaboud (Routledge, 2024)
This book presents Urbal, an approach that applies impact pathway mapping to understand how food system innovations in cities, and their territories, change and impact food system sustainability. Around the world, people are finding innovative ways to make their food systems more sustainable. However, documenting and understanding how these innovations impact the sustainability of food system can be a challenge. The Urban Driven Innovations for Sustainable Food Systems (Urbal) methodology responds to these constraints by providing innovations with a simple, open-source, resource-efficient tool that is easily appropriated and adaptable to different contexts. Urbal is designed to respond to the demands of field stakeholders, whether public or private, to accompany and guide them in their actions and decision-making with regard to sustainability objectives. This book presents this qualitative and participatory impact assessment method of food innovations and applies it to several cases of food innovation around the world, including the impact of agricultural districts in Milan, chefs and gastronomy in Brasilia, e-commerce in Vietnam, eco-friendly farm systems in Berlin and the Nourish to Flourish governance process in Cape Town. The book demonstrates how food innovations can impact different dimensions of sustainability, positively and negatively, and identify the elements that facilitate or hinder these impacts. The volume reflects on how to strengthen the capacity of these stakeholders to disseminate their innovations on other scales to contribute to the transition towards more sustainable food systems. This book will be of great interest to students and scholars working on sustainable food systems, urban food, food innovation and impact assessment, as well as policymakers, practitioners and funders interested in these areas.
Keywords: 330; agriculture; cities; food; sustainability; systems